Inheritance Counseling and Mediation as Conflict Resolution in Contemporary Indonesian Muslim Families - Endah Mustika Pertiwi; Elvi Soeradji; Surya Sukti (UIN Raden Mas Said Surakarta, 2025)
Inheritance disputes within Indonesian Muslim families often involve complex legal, social, and emotional dimensions shaped by Islamic law, state regulations, and customary practices. This article examines the role of inheritance counseling and mediation as non-litigation mechanisms for resolving inheritance disputes and preserving family harmony. Using a qualitative normative–empirical approach, the study combines field research conducted in Palangka Raya with an analysis of Islamic inheritance principles (fiqh al-mawārīth) and contemporary mediation frameworks. The findings demonstrate that inheritance counseling enhances legal awareness, clarifies rights and obligations among heirs, and prevents conflict escalation at an early stage. Mediation-based dispute resolution is shown to be more efficient, less costly, and more conducive to maintaining kinship relations than litigation. However, institutional mediation bodies remain underutilized due to limited public awareness and accessibility. This study contributes to Islamic family law scholarship by highlighting the integration of Sharīʿa-based inheritance norms with restorative and community-oriented mediation practices within Indonesia’s plural legal system.